Associated benefits of manatee watching in the Costa dos Corais Environmental Protection Area - Izidoro, Flávia Bonfietti; Schiavetti, Alexandre (Frontiers in Marine Science, 2022)
Marine mammals provide diverse and interconnected ecosystem services. According to the literature, the use of these services is associated with human needs related to provision, ecosystem regulation, education, culture, spirituality, and recreation. Tourism with marine animals can provide psychological benefits, emotional connection, fun, and learning, in addition to generating high income in local communities. This study aimed to determine the willingness to pay of the community and visitors for the conservation of the West Indian manatee (Trichechus manatus), identify the revenue from manatee watching, and evaluate well-being according to the participants of this attraction. The study was conducted from January 2020 to February 2021, in the Costa dos Corais Environmental Protection Area, Brazil. Data were collected using questionnaires and specific forms for the seven categories of social actors involved with manatee watching. The contingent valuation method was used to evaluate the willingness to pay of the respondents for the conservation of the manatee. The willingness of individuals to conduct voluntary work was also considered and subsequently converted into monetary values. Revenue from manatee watching was calculated through the direct costs of acquiring tour tickets and indirect expenditure on accommodation, food, transportation, and souvenirs. The feelings of the tourists who completed the trip were determined using a semi-structured question and their level of satisfaction was established using a five-point Likert scale. A total of 761 interviews were conducted. Most of the survey respondents were female, with a high level of education, and with a median monthly income of USD 1 800 dollars. The average mean value declared for willingness to pay was USD 3.6 dollars per month. The median hours devoted to volunteer work were 60 hours per year, which is the equivalent of USD 2.59 dollars per month. Direct revenue from this form of tourism was USD 125 595 dollars and total projected revenue was USD 15 392 225.45 dollars in the studied period. The vast majority of tourists managed to see the manatee and declared positive feelings after the trip. We believe that more elaborate promotion of manatee-watching would attract a higher number of tourists to the protected area.